Effect of trandformational leadership and organizational culture on employee performance on PT. Bank Tabungan Negara (Persero) branch Pekanbaru - Magdalena, Susi; ', Marnis; ', Sjahruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted on Bank Tabungan Negara (PERSERO) branch Pekanbaru. The purpose of this study was to determine the effect of transformational leadership and organizational culture om employee performance on Bank Tabungan Negara (PERSERO) branch Pekanbaru and also to find out which factors affect the performance of the more dominant. The population in this study were all employee of PT. Bank Tabungan Negara (PERSERO) branch Pekanbaru, up to December 2012 quantity f employee in Bank Tabungan Negara Pekanbaru is 72 people and all of them were sampled, so that the method of data collection is done by census.Based on the research results and discussion it is know that the leadership and organizational culture have a significant effect on performance of employees simultanceously on PT. Bank Tabungan Negara (PERSERO) branch Pekanbaru. Transformational leadership and organizational culture partially significant effect on employee performance on Bank Tabungan Negara (PERSERO) branch Pekanbaru. Transformational leadership and organizational culture has contributed a high and strong relationships to employee performance PT. Bank Tabungan Negara (PERSERO) branch Pekanbaru.Keyword : Performance, Transformational Leadership, Organizational Culture